Do Entrepreneurial Marketing Strategies Lead to Better Marketing Performance on SMES? - Koeswandi, Tika; Gaffar, Vanessa; Wibowo, Lili Adi; Primaskara, Ery Adam (Image : Jurnal Riset Manajemen, 2024)
This research aims to describe and find out how entrepreneurial marketing influences the marketing performance of Small and Medium Enterprises in West Java Province. This research involved 159 Small and Medium Enterprises that had been in business for at least 5 years and also received training and mentoring on marketing from both the government and private sector. Data analysis uses linear regression. This study found that there was a positive impact from Entrepreneurial Marketing Strategies (EMS) toward the SMEs' Marketing Performance (MP). It concludes that Entrepreneurial marketing strategies have been shown to lead to better marketing performance in Small and Medium Enterprises (SMEs). The more successful the entrepreneurial marketing strategy is implemented, the better marketing performance occurs. This research provides important implications that the use of Entrepreneurial Marketing Strategy can be a key factor in improving the marketing performance of Small and Medium Enterprises in West Java Province. This shows the need for further support from both the government and the private sector in providing marketing training and mentoring to SMEs to strengthen competitiveness and regional economic growth.